Rapid detection of adulterated fermented maize (Ogi) with sorghum leaf sheath (Poroporo) using visible-near infrared spectroscopy - Onifade, J.O. (University of Ibadan, 2022)
Food adulteration is a very old and common problem, which is often seen in both the low-and middle-income countries and even in some developed countries. Maize-based porridge especially ogi is a high-value commodity and common indigenous complementary food that is a target for adulteration, leading to loss of quality and encroachment on the rights and interests of consumers. This study investigated the characterization of the microorganisms found in ogi fermented for 0 to 120 hours and the feasibility of using visible - near Infrared (VIS-NIR) spectroscopy combined with multivariate analysis for detection and quantification of ogi adulterated with sorghum leaf sheath extract at different concentrations. NIR spectra of the adulterated and pure ogi were measured between the regions 400 – 2498 nm. The multivariate methods included Principal component analysis (PCA), multiplicative scatter correction (MSC), Savitzky-Golay derivatization, and partial least square – discriminant analysis (PLS-DA). PCA gave visible cluster trends for authentic samples and adulterated ones. PLS-DA was used to detect the discrimination between the pure and adulterated ogi samples. The PLS-DA model with MSC and fist derivative Savitzky-Golay normalization with five smoothing points was able to cross validate adulteration better at 5% adulteration level successfully compared to other adulteration levels. Standard microbiological characterization of the isolates conducted and results revealed that Saccharomyces cerevisiae, Candida and Lactobacillus species were the main microorganisms found in the fermentation medium within 96 hours of fermentation. There was an increase in the population of the bacteria and yeasts (measured in CFU ml-1) as the fermentation progressed. The results suggested that the predominant microorganisms during the fermentation period was the LABs and that NIR spectroscopy associated with multivariate analysis has the great potential for a rapid and non-destructive detection of adulteration in maize gruel (ogi).